Contact Tracing and Quarantine for Covid 19: Challenges in community surveillance - Gowda, Giriyanna; Holla, Ramesh; Ramraj, Balaji; Shettihalli Gudegowda, Kishore (Indian Journal of Community Health, 2020)
Covid 19 caused by SARS-coV-2 is a novel corona virus. This began in Wuhan city, China at the end of December 2019 and had spread to the rest of the world. World Health Organization (WHO) declared Covid 19 as Public Health Emergency of International Concern (PHEIC) on 30th Jan 2020 and later declared as pandemic on 11th march 2020. 1 The disease is mainly spread from human to human through small droplets from nose or mouth when a person with Covid 19 coughs or exhales and through the surface contact. Community surveillance plays significant role in prevention of spread of disease. It includes isolation of the positive case, quarantine of the high risk and low risk contacts and community disinfection.1, 2 The period of communicability is estimated with the current data to be from 2 days before the onset of symptoms and up to 2 weeks after onset. Hence the initial few asymptomatic days turns out to be crucial period in containing the spread of infection. By the time a Covid 19 patient is diagnosed and isolated, there are quite a number of primary and secondary contacts. Government of India focus has been on Community Surveillance activities which mainly comprises of Contact Tracing and Quarantine.3, 4 This article focuses on the various measures taken to trace the contacts, quarantine measures and on the challenges faced.